Some Aspects of the Formation and Development of the Jury in Foreign Countries and in Kazakhstan - KOZHAKHMETOV, Galym; RAKHIMGULOVA, Manshuk (Journal of Advanced Research in Law and Economics, 2017)
The article introduce institution of the jury did not go unnoticed by society. Opinions were divided, someone fully supports this institution, considering it a manifestation of democracy and someone on the contrary, believes that this is the work of professionals. This article discusses the problems associated with the need for and operation of the jury trial in the Republic of Kazakhstan. Not denying the fact that the institution of trial by jury has its shortcomings, we consider it necessary to stress that raise questions and hold court session with the participation of a professional judge, but this is not a debate about its liquidation. Trial by jury is a link between society and the state, it portends justice is not only the government, but also in the general population than the prestige of the judicial system and the state. Institute of jury trial has shown its worth, the need for the existence within a given society, as evidenced by the statistical results of the practice of law, articles of scientific and practical workers. On this basis, we believe: it is necessary to debate on how to improve the activities of the institute of juries.